Satellite radar interferometry for the analysis of potential instability in urban areas of high historical and cultural value - Palamidessi, Anna; Bianchini, Silvia; Centauro, Irene; Tofani, Veronica; Tapete, Deodato; Virelli, Maria (Italian journal of engineering geology and environment, 2024)
Satellite radar remote sensing techniques are non-invasive methodologies that can be effectively used for diagnostic purposes, measuring displacements, and monitoring cultural assets, architectural structures, and archaeological areas without injuring their integrity. The environmental condition and hydrogeological hazard in the Italian territory could make its invaluable Cultural Heritage at risk. Therefore, within the National Extraordinary Plan for Monitoring and Conservation of Cultural Heritage, an agreement has been established between the Ministry of Culture and the UNESCO Chair of the UNiversity of Florence on Prevention and Sustainable Management of Geo-hydrological Hazard to analyse ground motion rates on built-up areas by means of acquisition and PSI (Persistent Scatterers Interferometry) elaboration of high-resolution Cosmo-SkyMed synthetic aperture radar (SAR) satellite data (X-band). This technique can provide useful support on the conservation and protection of Cultural Heritage, as it endorses an innovative perspective on the condition and safety of historical sites, monuments, archaeological sites and artworks, thus contributing significantly to their preservation over time. Through SAR interferometric techniques, it is possible to identify millimetric displacements related to environmental threats, such as slow-moving landslides. This work proposes the classification of buildings of urban areas by using two indices based on PSI data coverage and deformation rates: the data coverage index in each building (Id) and the average velocity index of PSI data in each building and its surroundings (Ivmean), representing deformation rates in a locally scaled, easily understandable color-coded format. This method has already been tested in scientific literature on other SAR datasets for evaluating instability at the building scale. The approach aims to develop a fast and low-cost system to assess buildings that are potentially exposed to deformation and therefore more susceptible to damage in heavily urbanized areas with high historical-cultural value. In order to safeguard Cultural Heritage from natural disasters, the proposed methodology integrates a high degree of scientific and technological expertise and presents an updated and accurate screening of potential deformations due to hydrogeological hazards.